Expression of DUX4 in zebrafish development recapitulates facioscapulohumeral muscular dystrophy - Mitsuhashi, Hiroaki (Oxford University Press, 2013)
Facioscapulohumeral muscular dystrophy (FSHD) is a common form of muscular dystrophy characterized by an asymmetric progressive weakness and wasting of the facial, shoulder and upper arm muscles, frequently accompanied by hearing loss and retinal vasculopathy. FSHD is an autosomal dominant disease linked to chromosome 4q35, but the causative gene remains controversial. DUX4 is a leading candidate gene as causative of FSHD. However, DUX4 expression is extremely low in FSHD muscle, and there is no DUX4 animal model that mirrors the pathology in human FSHD. Here, we show that the misexpression of very low levels of human DUX4 in zebrafish development recapitulates the phenotypes seen in human FSHD patients. Microinjection of small amounts of human full-length DUX4 (DUX4-fl) mRNA into fertilized zebrafish eggs caused asymmetric abnormalities such as less pigmentation of the eyes, altered morphology of ears, developmental abnormality of fin muscle, disorganization of facial musculature and/or degeneration of trunk muscle later in development. Moreover, DUX4-fl expression caused aberrant localization of myogenic cells marked with α-actin promoter-driven enhanced green fluorescent protein outside somite boundary, especially in head region. These abnormalities were rescued by coinjection of the short form of DUX4 (DUX4-s). Our results suggest that the misexpression of DUX4-fl, even at extremely low level, can recapitulate the phenotype observed in FSHD patients in a vertebrate model. These results strongly support the current hypothesis for a role of DUX4 in FSHD pathogenesis. We also propose that DUX4 expression during development is important for the pathogenesis of FSHD.